Solution of the Time-Dependent Schrödinger Equation by the Laplace Transform Method - Lin, S. H. (1971)
The time-dependent Schrödinger equation for two quite general types of perturbation has been solved by introducing the Laplace transforms to eliminate the time variable. The resulting time-independent differential equation can then be solved by the perturbation method, the variation method, the variation-perturbation method, and other methods.